Neglected Intrauterine Device Migration Complications: Case Reports - Audrey S. Koh (Women's Health Reports, 2023)
This series of four cases describes unusual intrauterine device (IUD) migration complications, associated etiologic factors, and their management. Recent increases in sociopolitical and medical forces worldwide contributed to inattention to these patients with subclinical IUD complications. The international movement of patients, delays in gynecologic care due to the COVID-19 pandemic, lack of health care access, shifts away from annual examinations, and patients' lack of medical records or IUD awareness can lead to long durations of neglected IUDs and associated complications. These complications might have been avoided or minimized with regular gynecologic health care. Physicians should consider moving toward routine examinations of all IUD patients, rather than away from annual examinations as has been promulgated by some medical societies. Patient education is needed on the importance of routine monitoring of IUDs and retention of device records. Clinicians should become familiar with IUDs from around the world as well as devices no longer being prescribed, as their appearance, associated complications, and presentations may differ from locally currently available devices.